IMPLMENTASI EVALUASI PEMBELAJARAN MODEL GAMIFICATION DALAM PELAJARAN PENDIDIKAN AGAMA ISLAM PADA ASPEK AFEKTIF SISWA DI SMK NEGERI 2 BENGKULU UTARA - Pristiana (Yayasan Darussalam Bengkulu, 2022)
Learning activities can not be separated from the role of a teacher who serves as the manager of learning in the classroom and uses various ways to achieve the learning objectives that have been set. This is inseparable from the applied learning model/method. The purpose of this study is to describe the implementation, inhibiting factors and supporting evaluation of gamification model learning in Islamic religious education lessons on the affective aspects of students at SMK Negeri 2 Bengkulu Utara. This study uses a type of field research (field research) with a qualitative approach. The method used is descriptive research. Subjects in this study were waka curriculum, PAI teachers and student representatives. Data collection techniques using observation, interviews, and documentation. Based on the results of the study, it can be concluded that the evaluation of gamification model learning in Islamic religious education lessons on the affective aspects of students at SMK Negeri 2 Bengkulu Utara can increase student interest and motivation, which can be seen in how children respond to learning, complete tasks given, and pay attention to the material presented. delivered, and several supporting factors, namely the availability of wifi, student interest, teacher readiness, available media infocus and inhibiting factors in the form of weak wifi signals, requiring time to coordinate children